2019
DOI: 10.1155/2019/3185286
|View full text |Cite
|
Sign up to set email alerts
|

Knee Sepsis after Suprapatellar Nailing of an Open Tibia Fracture: Treatment with Acute Deformity and External Fixation

Abstract: Case A 31-year-old male was involved in a dirt bike accident and sustained an isolated type II open mid-distal tibia fracture. The patient underwent suprapatellar intramedullary nailing and subsequently developed knee sepsis. Conclusion This patient was managed with irrigation and debridements of the knee, fracture site, and intramedullary canal. A resultant soft-tissue defect over the fracture site obviated primary closure. Creation of an acute deformity stabilized by a Taylor spatial frame allowed primary wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Hence, a DTF can be reduced and persistently maintained during medullary canal preparation and IMN placement [ 8 ]. However, the application of these techniques is concerning owing to their intra-articular nature, as they can have complications such as knee cartilage damage [ 9 , 10 ], septic arthritis [ 11 ], and heterotopic ossification [ 12 ]. In addition, the application of the SP IMN technique requires special surgical instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a DTF can be reduced and persistently maintained during medullary canal preparation and IMN placement [ 8 ]. However, the application of these techniques is concerning owing to their intra-articular nature, as they can have complications such as knee cartilage damage [ 9 , 10 ], septic arthritis [ 11 ], and heterotopic ossification [ 12 ]. In addition, the application of the SP IMN technique requires special surgical instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The Taylor spatial frame (TSF) was the only hexapod system described in the literature review. 11 – 13 , 15 , 27 , 43 , 44 The uses of the TSF for the correction of temporary deformities created for closing soft tissue defects have the following disadvantages:…”
Section: Discussionmentioning
confidence: 99%
“…reported iatrogenic injuries following suprapatellar nailing of an open tibial fracture, along with septic arthritis (23). Recently, Rehman et al reported a case of heterotopic ossi cation following suprapatellar nailing (24).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it promotes intraoperative imaging and optimizes the positioning of the implant (13,(18)(19)(20)(21). However, some studies have expressed their concerns, regarding the possibility of heterotopic ossi cation, knee cartilage injury, knee sepsis, and nail removal (3,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%